STUDI DESKRIPSI SISTEM PERPARKIRAN DI GALERIA MALL YOGYAKARTA - Retna Hidayah, Tryas Purnama (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT This study is aimed to describe the eligibility of parking system at Galeria Mall Yogyakarta in parking vehicle based on the standard of the Director General of Land Transportation and NAASRA. The subjects of this study are parking spaces at Galeria Mall Yogyakarta, located on Prof.Ir.Yohanes Street. The object of this study is the number of parking spaces available, patterns and dimensions of the parking space, the dimensions of crossing tracks. The data collection is done by conducting observation and field documentation. The findings of this study which have been conducted indicate that: 1) In terms of quantity, the capacity of car parking spaces: providing only 69% (149 units) out of 214 units that do not meet the standards of calculation of Director General of land transportation, worth 2.8 / 100m² from 5.5/100m² so it does not meet the NAASRA standards. While motorcycle parking space capacity provides 106% (408) out of 385 units so that it meets the standards of calculation. 2) In terms of quality of SRP car parking area meets the standards: the parking angle and the parking spaces are effective, Modules, Bp, Lp. SRP B1 floor car area meets the standards: the parking angle and the parking spaces are also effective, car area on Bp, Lp. SRP B2 Floor meets the standards: the parking angle and the parking spaces are effective (C1, C2, C3), module, the furthest width of parking space (C1, C2, C3), Bp (C1, C3), Lp (C1, C2, C3). SRP Floor B2 motorcycle area meets the standards: the parking angle and the parking spaces are effective. Keywords: Dimension, Crossing Track, Capacity, Parking Space, SRP